Milk quality and somatic cell count comparison in raw whole milk before and after the filtering. - WingChing-Jones, Rodolfo (2013)
The purpose of this work was to evaluate the effect of filtering raw cattle milk with a mixed membrane. This research was conducted in the Dairy-SDA Module at the University of Costa Rica, between May 10th and Febuary 2011, where milking is performed automatically with aid of a system of jar collectors. Samples of 100 ml of milk were taken from 112 jars before and after filtering using a funnel. Milk components determinations were performed using the FOSS Electric A/S for the MilkoScanTM Type 71200 FT 120 equipment, while a somatic cell count was performed according to the methodology described for Fossomatic Series 400. Protein, lactose and somatic cell milk content did not change significantly, while fat milk content and milk total solids percentage were affected by the filtering practice. This reduction resulted in a decrease of 3.04% of total revenue from the sale of milk.